Dehydroflavonolignans from Silymarin Potentiate Transition Metal Toxicity In Vitro but Are Protective for Isolated Erythrocytes Ex Vivo - Zuzana Lomozová; Václav Tvrdý; Marcel Hrubša; Maria Carmen Catapano; Kateřina Macáková; David Biedermann; Radim Kučera; Vladimír Křen; Přemysl Mladěnka; Kateřina Valentová (Antioxidants, 2021)
2,3-Dehydrosilybin (DHS) was previously shown to chelate and reduce both copper and iron ions. In this study, similar experiments with 2,3-dehydrosilychristin (DHSCH) showed that this congener of DHS also chelates and reduces both metals. Statistical analysis pointed to some differences between both compounds: in general, DHS appeared to be a more potent iron and copper chelator, and a copper reducing agent under acidic conditions, while DHSCH was a more potent copper reducing agent under neutral conditions. In the next step, both DHS and DHSCH were tested for metal-based Fenton chemistry in vitro using HPLC with coulometric detection. Neither of these compounds were able to block the iron-based Fenton reaction and, in addition, they mostly intensified hydroxyl radical production. In the copper-based Fenton reaction, the effect of DHSCH was again prooxidant or neutral, while the effect of DHS was profoundly condition-dependent. DHS was even able to attenuate the reaction under some conditions. Interestingly, both compounds were strongly protective against the copper-triggered lysis of red blood cells, with DHSCH being more potent. The results from this study indicated that, notwithstanding the prooxidative effects of both dehydroflavonolignans, their in vivo effect could be protective.